2018
DOI: 10.1128/iai.00787-17
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental Influence of Alveolar Macrophages on Protective Humoral Immunity during Francisella tularensis SchuS4 Pulmonary Infection

Abstract: Opsonizing antibody is a critical component of the host protective immune response against many respiratory pathogens. However, the role of antibodies in protection against pulmonary infection with highly virulent strain SchuS4 is unclear, and the mechanism that allows to evade antibody-mediated bacterial clearance is not fully understood. We have now found that depletion of alveolar macrophages reveals an otherwise cryptic protective effect of opsonizing antibody. While antibody opsonization alone failed to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…Francisella tularensis live vaccine strain (LVS) containing pKK214kanGFP [41] was grown in brain–heart infusion with 1% isovitalex (BD biosciences, San Jose, CA, USA) and 15 µg·mL −1 kanamycin at 37 °C. Francisella tularensis ShuS4 was grown overnight in Muller–Hinton broth supplemented with isovitalex, as described elsewhere [42]. Bacteria were washed and resuspended in PBS, then diluted in RPMI + 10% FBS + GM‐CSF and added to transfected AM‐MDMs to a final MOI 10.…”
Section: Methodsmentioning
confidence: 99%
“…Francisella tularensis live vaccine strain (LVS) containing pKK214kanGFP [41] was grown in brain–heart infusion with 1% isovitalex (BD biosciences, San Jose, CA, USA) and 15 µg·mL −1 kanamycin at 37 °C. Francisella tularensis ShuS4 was grown overnight in Muller–Hinton broth supplemented with isovitalex, as described elsewhere [42]. Bacteria were washed and resuspended in PBS, then diluted in RPMI + 10% FBS + GM‐CSF and added to transfected AM‐MDMs to a final MOI 10.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, opsonization of bacteria prior to engulfment by phagocytes improves their intracellular destruction, as Fc receptor mediated phagocytosis was associated with major superoxide production, a rapid NADPH dependent oxidative burst, and a restriction of the phagosomal escape [36]. A recent study showed a protective effect of opsonizing antibodies against highly virulent Francisella tularensis pulmonary infection in mice depleted in alveolar macrophages [37]. According to this information, patients with B cell depletion might present a higher susceptibility to tularemia.…”
Section: Host Immunity Against Francisellamentioning
confidence: 98%
“…Similarly, R. parkeri , a member of the spotted fever group, was detected in A. americanum tick hemocytes >1 month after infection, providing further evidence that tick hemocytes may not clear all bacterial infections and suggesting that some bacteria may evade tick humoral immune responses by infecting hemocytes [ 125 ]. Parallel comparisons have been made to help explain why F. tularensis infects mammalian macrophages—to evade humoral immune responses (e.g., antibodies) and other host immune responses [ 126 , 127 ]. Clearly, studies are needed to examine how D. variabilis and A. americanum (and potentially other ticks) hemocytes interact with F. tularensis and whether F. tularensis infects tick hemocytes to evade extracellular immune responses.…”
Section: The Tick Immune System and Antimicrobial Activitiesmentioning
confidence: 99%